2021
DOI: 10.1016/j.amepre.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Technologies to Reach Tobacco Users Who Want to Quit: Evidence From the National Cancer Institute's Smokefree.gov Initiative

Abstract: The rapid growth of smartphone ownership and broadband access has created new opportunities to reach smokers with cessation information and support using digital technologies. These technologies can both complement and be integrated with traditional support modalities such as telephone quitlines and 1-on-1 clinical cessation counseling. The National Cancer Institute's Smokefree.gov Initiative provides free, evidence-based cessation support to the public through a multimodal suite of digital interventions, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In line with previous research (Phillips et al, 2017(Phillips et al, , 2019, online was identified as a favorable mode of delivery among some participants. The use of technology as a mode of delivery could provide an opportunity to reach a larger target population (Prutzman et al, 2021) and may open the door for a more diverse crowd of participants and instructors/facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research (Phillips et al, 2017(Phillips et al, , 2019, online was identified as a favorable mode of delivery among some participants. The use of technology as a mode of delivery could provide an opportunity to reach a larger target population (Prutzman et al, 2021) and may open the door for a more diverse crowd of participants and instructors/facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that discrepancies in the timing and magnitude of increases and decreases in traffic on SmokeFree digital platforms could be attributed to several factors-mainly the medium of the platform, the aim of the public health effort, and the target audience. However, despite the modest increases and decreases in SmokeFree traffic, these changes are meaningful due to the reach of SmokeFree platforms [35]. It is well documented that the impact of public efforts (eg, interventions) are a product of reach and effectiveness [71].…”
Section: Principal Findingsmentioning
confidence: 99%
“…One such suite of digital platforms that is freely available to smokers in the United States is the National Cancer Institute's SmokeFree.gov initiative (SFGI) [33,34]. Initially, the SFGI had a single website that launched in 2003 [35]. The SFGI now has multiple platforms, including the main SFGI website, 6 social media accounts, 2 mobile apps (ie, QuitGuide and quitSTART), and 6 SMS text messaging interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prutzman et al 16 describe how the widespread adoption of the Internet and mobile technologies has transformed how individuals seek information about health topics, including quitting smoking, creating the impetus for innovation. In complement to live support through telephone-based quitlines, website-and mobile-based smoking cessation interventions provide an opportunity to significantly expand public access to evidence-based treatment.…”
Section: Innovatementioning
confidence: 99%